ANALISIS RESIKO USAHATANI KOPI ROBUSTA BERDASARKAN SISTEM VEGETATIF DAN GENERATIF DI DESA GALANG TINGGI KECAMATAN MEKAKAU ILIR KABUPATEN OGAN KOMERING ULU SELATAN (JASEP, 2020)
This study aims to analyze how the cost risk, production,selling price, coffe farm income with vegetative and generative system. This research is carried out in the Village of Galang TinggiSub- district ofMekakau IlirRegency Ogan Komering Ulu Selatan. Selected this area as a Research location based on data obtained from the Agriculter and Plantation Districts Ogan Komering Ulu Selatan, that coffe farming robusta land area and production is greater than other villages. The implementation of the study was conducted for 3 Month from November – January. Starting from the preparation of proposals, data retrieval, data processing and preparation of final reports. The method used is survey method. From the calculation it can be seen the risk of robusta coffe farming system is smaller than the generative system. The small coefficient value indicates that the average value variability in the farm is low. This ilistrates the risk that will be faced in the small vegetative system while the generative system is larger.